Increasing Research Capacity in Underserved Communities: Formative and Summative Evaluation of the Mississippi Community Research Fellows Training Program (Cohort 1) - Fastring, Danielle; Mayfield-Johnson, Susan; Funchess, Tanya; Green, Candice; Walker, Victoria; Powell, Georgette (Frontiers in Public Health, 2018)
Background: The Mississippi Community Research Fellows Training Program (MSCRFTP) is a 15-week program conducted in Jackson, Mississippi consisting of training in the areas of evidence-based public health, research methods, research ethics, and cultural competency. The purpose of the program was to increase community knowledge and understanding of public health research, develop community-based projects that addressed health disparity in the participants’ community, increase individual and community capacity, and to engage in a community members as equal partners in the research process. Methods: A comprehensive evaluation of the MSCRFTP was conducted that included both quantitative and qualitative methods. All participants were asked to complete a baseline, midterm, and final assessment as part of their program requirements. Knowledge gained was assessed by comparing baseline assessment responses to final assessment responses related to 27 key content areas addressed in the training sessions. Assessments also collected participants’ attitudes toward participating in research within their communities, their perceived influence over community decisions, and perceptions of community members’ involvement in research, satisfaction with the program, and the program’s impact on the participants’ daily practice and community work. Results: Twenty-one participants, the majority of which were female and African American, completed the MSCRFTP. Knowledge of concepts addressed in 15 weekly training sessions improved significantly on 85.2% of 27 key areas evaluated (p<0.05). Two mini-grant Community Based Participatory Research projects proposed by participants were funded through competitive application. Most participants agreed that by working together, the people in their community could influence decisions that affected the community. All participants, rated their satisfaction with the program overall as ‘very high’ (76.2%, n=16) or ‘high’ (23.8%, n=5). Conclusion: The evaluation of the MSCRFTP demonstrates that participants have the necessary knowledge to engage as research partners, and the pilot projects provided an opportunity for application of this objective to be realized. Overall, the MSCRFTP was an intervention that assisted to help community members identify their community strengths and weaknesses, interpret knowledge in a meaningful way, and create a self-reflective community of inquiry for change.